PATHOGENICITY STUDY OF FIELD ISOLATES OF AVIBACTERIUM PARAGALLINARUM IN SEVEN WEEK OLD CHICKS. - Durairajan Ramachandran; Vadivazhagan Kalimuthu; Mandeep Sharma (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Avibacterium paragallinarum isolated from various places in northern India were studied for their virulence by infecting the experimental chicks. An inoculum of 0.2 ml (1011 cfu/ml) was dropped in the nostrils of birds or injected in the right infraorbital sinus of three seven-week-old chickens for each isolate. Birds infected with A. paragallinarum showed typical signs of Infectious Coryza. Bacteria could be reisolated from the birds. The identified bacteria and the direct clinical samples subjected to species specific HP2PCR for A.  paragallinarum. PCR was found to be specific and it produced 500bp amplicons. In the challenge study on the experimental birds, accumulation of whitish fluid like exudates in the infraorbital sinuses was more prominent and air sacculitis and pneumonia noticed less frequently in birds.